RAG-Mediated V(D)J Recombination Is Not Essential for Tumorigenesis in Atm-Deficient Mice - Petiniot, Lisa K. (American Society for Microbiology, 2002)
Atm-deficient mice die of malignant thymic lymphomas characterized by translocations within the Tcrα/δ locus, suggesting that tumorigenesis is secondary to aberrant responses to double-stranded DNA (dsDNA) breaks that occur during RAG-dependent V(D)J recombination. We recently demonstrated that development of thymic lymphoma in Atm(−/−) mice was not prevented by loss of RAG-2. Thymic lymphomas that developed in Rag2(−/−) Atm(−/−) mice contained multiple chromosomal abnormalities, but none of these involved the Tcrα/δ locus. These findings indicated that tumorigenesis in Atm(−/−) mice is mediated by chromosomal translocations secondary to aberrant responses to dsDNA breaks and that V(D)J recombination is an important, but not essential, event in susceptibility. In contrast to these findings, it was recently reported that Rag1(−/−) Atm(−/−) mice do not develop thymic lymphomas, a finding that was interpreted as demonstrating a requirement for RAG-dependent recombination in the susceptibility to tumors in Atm-deficient mice. To test the possibility that RAG-1 and RAG-2 differ in their roles in tumorigenesis, we studied Rag1(−/−) Atm(−/−) mice in parallel to our previous Rag2(−/−) Atm(−/−) study. We found that thymic lymphomas occur at high frequency in Rag1(−/−) Atm(−/−) mice and resemble those that occur in Rag2(−/−) Atm(−/−) mice. These results indicate that both RAG-1 and RAG-2 are necessary for tumorigenesis involving translocation in the Tcrα/δ locus but that Atm deficiency leads to tumors through a broader RAG-independent predisposition to translocation, related to a generalized defect in dsDNA break repair.